Capturing invisible dimensions of terrorist victimisation through photography and video: Theoretical background for a research in progress in the Basque country - Varona Gema (Temida)
Memorialisation is experienced by victims of traumatic events as a form of justice. Victims‘ and society right to memory is mentioned in the Basque Law 4/2008 on recognition and protection of terrorism victims and the Spanish Law 29/2011 on recognition and integral protection of terrorism victims. Drawing from critical victimology and memory studies, this contribution aims at addressing current criticism by some victims‘ organizations with regard to memory public policies in this field. It particularly addresses ways of restoration through memory linked to the meaning of spaces of victimisation by examining the work of different photographers on making aspects of those victimisations visible for the contested purpose of remembering. First the conceptual framework on space, victimisation and memory is presented. Then it is related to the results of qualitative research by the Basque Institute of Criminology. At the end the micro, meso and macro aspects of local intervention proposals on restorative memory, including ethical remarks are commented.